E0387 Percutaneously intervention was successfully performed in right coronary artery combined with right sinus of valsalva aneurysm. (17th November 2010) - Fan, Liu; Jingchao, Lu; Wei, Cui; Guoqiang, Gu; Xiuchun, Yang; Ruiqin, Xie; Jie, Hao; Weina, Pei; Baohua, Li
Abstract : Introduction: Sinus of Valsalva aneurysms (SVA) are rare cardiac anomalies. They may be congenital or acquired and are usually asymptomatic unless complicated by such developments as intracardiac rupture with formation of a fistula or aortic valvular insufficiency. The following case is unusual in that the presenting symptom was angina pectoris due to severe atherosclerotic coronary disease with development of an aneurysm of the sinus of Valsalva secondary to atherosclerotic involvement of the aorta. Case report: A 50-year-old male patient presented with 2-week history of increasing exertional chest pain and intermittent chest pain at rest for 1 week. Echocardiography as well as contrast enhanced aorta CT revealed dilatation and irregular protrusion of the right sinus of Valsalva encroaching on right ventricular inflow tract. The aneurysm of the right sinus of Valsalva was about 4.2 cm in diameter. The aortic valve annulus and aortic valve leaflets were normal. Besides that, contrast enhanced aorta CT showed multiple spotted or comma calcification at aneurysm wall, and at the whole range of aorta accompany by irregular intima thickness. In addition, Selective coronary angiography showed 95% discrete diameter stenosis at the proximal segment of right coronary artery. A 50% and a 70% tubular diameter stenosis were separately noted at the proximal segment of left descending artery and at the origin of first diagonal branch. With these findings, severe coronary atherosclerosis combined with unruptured aneurysm of the right sinus of valsalva was diagnosed. Percutaneously coronary intervention (PCI) was successfully performed, and one drug-eluted stent was deployed in the proximal right coronary artery. There was no dissection at the localisation of stent and aortic root. Conclusions: In general, the surgical method for treating severe coronary heart disease associated with unruptured SVA generally consists of coronary artery bypass grafting and closure of the opening of the aneurysm. To our knowledge, it is the first report that percutaneously intervention was successfully performed in right coronary artery combined with right sinus of valsalva aneurysm. Thereby, PCI may be an alternative treatment strategy for this clinical situation.